Pengembangan Bahan Ajar Berbentuk Poster pada Tema Energi dan Perubahannya pada Siswa Kelas III SD Negeri 102011 Sei Buluh - Diah Utami; Fata Ibnu Hajar (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the process and analyze the feasibility of developing teaching materials in the form of posters on the theme of energy and its changes in third grade students of SD Negeri 102011 Sei Buluh. This research uses the ADDIE development model (Analyze, Design, Develop, Implementation and Evaluation) and the instruments used in this research are validation and needs questionnaire sheets. From the development process, a product is produced in the form of teaching materials in the form of posters that can be used in the learning process of the theme of energy and its changes. Then, the results of the feasibility of the material were obtained at 80% with